Combination Immunosuppression in IBD. Issue 3 (16th February 2018) - Bots, Steven; Gecse, Krisztina; Barclay, Murray; D'Haens, Geert
Abstract: Whether to use biologic treatment for inflammatory bowel disease as monotherapy or in combination with immunosuppressives has been a matter of debate in the last 2 decades. Combination therapy was not superior in any of the registration trials for Crohn's disease and ulcerative colitis for TNF antagonists, vedolizumab, or ustekinumab. It needs to be mentioned, though, that none of these trials were powered to detect such differences, and that many patients entered the trial after having failed conventional immunosuppressives. Postmarketing studies revealed that patients on background immunosuppression have a lower risk of immunogenicity (often resulting in infusion/injection reactions) than patients on monotherapy. In the SONIC and UC-SUCCESS trials, superiority of the combination azathioprine-infliximab was demonstrated in Crohn's disease and ulcerative colitis, respectively. This trial design has not been used with any other biologic for IBD, so far. Meanwhile, it has also become clear that combination treatment with TNF antagonists is associated with increased toxicity, mainly infections, but also malignancy such as lymphoproliferative disease. This toxicity could perhaps be reduced by using lower doses of immunosuppressives, a strategy that has been shown to be equally potent in reducing immunogenicity. Additionally, combination treatment could be used for a limited period of time (12 months or even shorter) since most immunogenicity develops in the beginning of the biologic treatment. Patients who develop anti-drug-antibodies later on can often be rescued by reintroduction of thiopurines or methotrexate. In summary, combination treatment is certainly beneficial with infliximab, at least in the first 12 months of treatment. With other TNF antagonists, vedolizumab, and ustekinumab, the available data do not offer clear guidance. In patients without increased risk of toxicity, and certainly in those with limited treatment options, it may be wise to offer combination treatment with all biologics for the time being and at least during the initiation phase.